Effectiveness of the heart technique (THT) therapy on students' emotional disorders - Sembiring, Mimpin; Tarigan, Thomas Natalisa; Lumbanbatu, Johannes Sohirimon; Tibo, Paulinus (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Students' emotional disorders are still a source of problems in the world of education.  This emotional disorder will influence their future and their adolescence itself. The other researcher has been done some therapy, but it doesn’t work enough to pretend the teenager’s emotional disorder. This research aims to offer a solution to the problem of emotional disorders, especially depression, anxiety, and panic disorders. The solution in question is an emotional therapy called The Heart Technique, which is part of hypnotherapy. The method used is a quantitative method with a quasi-experimental approach. The subjects of this research were Class XI SOS students at RK Serdang Murni Lubuk Pakam Private High School. SOS 1 class is the experimental class and SOS 2 class is the control class. Data processing was carried out using Excel and SPSS applications. The results of data processing show that the heart technique therapy is effective in reducing students' emotional disorders.